Improvement of Teacher Capability Using Contextual Teaching and Learning Models Through in House Training - Suhelmidam Suhelmidam (Universitas Riau, 2019)
The learning process at SMP N 6 Tualang is not satisfactory due to the relatively low teacher's competence. Therefore it is necessary to improve teacher quality. The improvement made is the ability to use the learning model. One of them is the use of the Contextual Teaching and Learning (CTL) model through In-House Training (IHT) activities. The purpose of this study is to describe and explain how effective the In House Training activities for improving teacher skills in the application of the CTL model. This study involved all teachers of SMP N 6 Tualang. The researcher conducted a pre-survey to find out the learning process in the classroom. Observation, Pre-test and interview techniques were also used to collect data. Each cycle's pre-test and post-test showed better improvement in the teacher's ability to apply this model. The teacher's assessment in designing the lesson plan learning model CTL in cycle 1 shows the average teacher's ability of 75.62% (good), in the second cycle it becomes 90.57% (very good). The results of supervision from 70.05% (good) in cycle 1, to 82.40% (good) in cycle 2, and teachers felt positive benefits from IHT activities. In conclusion, IHT activities were able to improve teacher competence using the CTL learning model.